Determinants of the Incidences of Dengue Hemorrhagic Fever in 2019 – 2021 - Hariyanto, Hendri; Sutiningsih, Dwi; Sakundarno, Mateus (Indonesian Journal of Global Health Research, 2024)
Dengue Hemorrhagic Fever (DHF) is an endemic disease transmitted by mosquitoes which has spread rapidly throughout the world, especially in Indonesia. Whereas in the working area of the Gunungpati Primary Health Care Centre the number of DHF cases increased by 128.57% in 2021.Objective: The objective of the study was to determine association related of the incidence of DHF in the working area of the Gunungpati Primary Health Care Centre in 2019-2021. Method: The research design used in this study was a correlational quantitative study. The sampling method using purposive sampling. Data collection in this study used secondary data sourced from the DHF Information System (Tunggal Dara) Semarang City Health Office for 2019-2021 was 30 people. Data were analyzed using the pearson correlation test. Results: The findings of this study were an overview of the incidences of DHF in the working area of the Gunungpati Primary Health Care Centre was 30, with the highest IR at the Jatirejo Village, 232.02 by 100,000 population. Based on the results of the bivariate analysis, it was found that only the variables sex (0.001) and ABJ (0.001) obtained P-value <0.05.Conclusions: The determinants associated with DHF cases in the working area of the Gunungpati Primary Health Care Centre were sex and ABJ with a correlation value of 1.000 and -1.000.